Translational considerations in injectable cell-based therapeutics for neurological applications: concepts, progress and challenges - Amer, Mahetab H.; Rose, Felicity R.A.J.; Shakesheff, Kevin M.; Modo, Michel; White, Lisa J. (Nature Publishing Group, 2017)
Significant progress has been made during the past decade towards the clinical adoption of cell- based therapeutics. However, existing cell delivery approaches have shown limited success, with numerous studies showing fewer than 5% of injected cells persisting at the site of injection within days of transplantation. Although consideration is being increasingly given to clinical trial design, little emphasis has been given to tools and protocols used to administer cells. The different behaviours of various cell types, dosing accuracy, precise delivery, and cell retention and viability post-injection are some of the obstacles facing clinical translation. For efficient injectable cell transplantation, accurate characterisation of cellular health post-injection and the development of standardised administration protocols are required. This review provides an overview of the challenges facing effective delivery of cell therapies, examines key studies that have been carried out to investigate injectable cell delivery, and outlines opportunities for translating these findings into more effective cell therapy interventions.